Efektivitas Penggunaan Media Berbasis Geogebra Pada Bangun Datar Dalam Pembelajaran Matematika Siswa Kelas V SDN 14 Ranah Pesisir - Lili Rismaini; Dewi Devita (STKIP Pesisir Selatan, 2024)
This research is motivated by the teacher-centered nature of current education. In recent years, the rapid advancement of information technology has significantly transformed how society seeks and acquires information. This technological progress has also influenced educational media, traditionally dominated by print-based learning materials used by teachers. The aim of this study is to enhance student learning outcomes through the use of GeoGebra-based media, which is effective in mathematics education. This research can be categorized as quantitative research with a quasi-experimental method. The study was conducted on fifth-grade students at SD N 14 Ranah Pesisir. The research instrument was developed to assess the effectiveness of using GeoGebra-based media in teaching planar geometry. The results of this study, analyzed using statistical methods including the Paired Sample Test, indicated a significance level (2-tailed) of 0.000, which is less than the alpha value of 0.05. This means that the significance value (0.000) is smaller than the alpha value (0.05), leading to the rejection of the null hypothesis (Ho) and the acceptance of the alternative hypothesis (Hi). Therefore, it can be concluded that there is a significant difference in students' mathematics learning outcomes before and after using GeoGebra in planar geometry instruction.